Peaks, valleys and vistas - Microsoft. (Economist, 2007)
The article discusses the Windows Vista computer operating system from Microsoft. The effect of the Internet on Microsoft is discussed. Most users are expected not to upgrade to Vista, bust instead buy it only when they buy a new computer. Computing trends affecting Microsoft include open-source software, online computer applications, and the rise of software as a service.